2016
DOI: 10.1177/1076029615627341
|View full text |Cite
|
Sign up to set email alerts
|

Higher CHA2DS2-VASc Score Is Associated With Increased Mortality in Acute Pulmonary Embolism

Abstract: Background: CHA 2 DS 2 -VASc score has been validated in risk prediction for stroke and thromboembolism in patients with atrial fibrillation (AF). Association of CHA 2 DS 2 -VASc score with higher risk of venous thromboembolism and pulmonary embolism (PE) has also been shown. In this study, we investigated the long-term prognostic value of CHA 2 DS 2 -VASc score in patients with acute pulmonary embolism (APE). Methods: Consecutive patients with APE presenting to our emergency department were retrospectively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…3,29,30 Furthermore, in a cohort of patients investigated for suspected PE, those in whom PE was excluded had a 6-month mortality, which was higher than those with proven PE 31 ; however, in the Multi-Ethnic Study of Atherosclerosis a high CACS was not associated with an increased risk of PE. 10 A prior history of cardiovascular disease 32 and a higher CHA2DS2-VASc score 33 have been shown to be associated with increased mortality in patients with acute PE. The presence of known coronary artery disease was associated with a 2.2-fold increase in allcause mortality at nearly 4 years of follow-up in a cohort study of 1,023 patients admitted with confirmed PE.…”
Section: Discussionmentioning
confidence: 99%
“…3,29,30 Furthermore, in a cohort of patients investigated for suspected PE, those in whom PE was excluded had a 6-month mortality, which was higher than those with proven PE 31 ; however, in the Multi-Ethnic Study of Atherosclerosis a high CACS was not associated with an increased risk of PE. 10 A prior history of cardiovascular disease 32 and a higher CHA2DS2-VASc score 33 have been shown to be associated with increased mortality in patients with acute PE. The presence of known coronary artery disease was associated with a 2.2-fold increase in allcause mortality at nearly 4 years of follow-up in a cohort study of 1,023 patients admitted with confirmed PE.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the score was matched against the outcomes of several diseases such as atrial fibrillation with pulmonary embolism, chronic obstructive pulmonary disease with or without AF, decreased left ventricular ejection fraction, and coronary artery disease. 12,21-25 In this study, we firstly investigated the association of the CHA2DS2-VASc score with the RVD, clinical subgroups, and in-hospital mortality. In addition to the abovementioned studies, in this study, we found that the CHA2DS2-VASc score was significantly different among the clinical subgroups in patients with acute PTE and determined that the CHA2DS2-VASc score was an independent predictor of the RVD in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of predicting all-cause mortality in systolic HF patients, R2CHADS2 seems to be the best of the three scoring systems, especially in systolic HF patients without AF [ 25 ]. Moreover, CHA2DS2-VASC score highly predicts all-cause mortality in patients’ acute ischemic stroke [ 26 ], ICD [ 27 ], and acute pulmonary embolism [ 28 ]. CHADS2, CHA2DS2-VASc and CHA2DS2-VASc-M (modified version of the CHA2DS2-VASc scoring system in which 1 point was assigned to male instead of female sex) have also been significantly associated with all-cause mortality in COVID-19 patients [ 29 ].…”
Section: Cha2ds2-vasc Score Predicts Mortality In Several Diseasesmentioning
confidence: 99%